Regional Government Policy in Protecting Customary Land Rights: A Case Study of the Toba Batak Indigenous Community - Janpatar Simamora (UIN Sunan Gunung Djati, 2025)
This study aims to examine the mechanism of recognition and implementation challenges concerning the Indigenous Peoples of Batak Toba Samosir, particularly in the protection of customary land rights, as regulated in Regional Regulation No. 1 of 2020 of Toba Samosir Regency. This research is significant considering that the protection of collective rights of indigenous peoples is a constitutional mandate often hindered by administrative and political constraints at the local level. Employing a normative juridical approach with a qualitative design, the unit of analysis comprises Regional Regulation No. 1/2020 and related legal frameworks. Data were collected through library research involving primary legal materials (legislation), secondary sources (academic literature), and tertiary sources (legal dictionaries and encyclopedias). The findings reveal that the recognition of customary territories is based on the principles of ripe-ripe (communal rights) and pangumpolan (individual rights), yet faces technical and administrative obstacles. These include the absence of a Regent Regulation (Perkada) as an operational guideline, the lack of valid spatial and historical data, and limited participation of indigenous communities in the verification process. This situation leads to inconsistencies between written legal norms and field implementation. The study highlights the need for regulatory synchronization between central and local governments, as well as the urgency of formulating an inclusive and implementable Perkada. The originality of this research lies in its focus on the tension between formal legal structures and customary norms within Indonesia's decentralized legal system.